Use of Unmanned Aerial Vehicles to Monitor Air Quality in Areas with Poor Accessibility. Case Study: the Orinoquia Natural Region, Colombia - Echeverri Londoño, Carlos Alberto; Maya Vasco, Gabriel Jaime (CIENCIA ergo-sum; Vol. 32 (2025): CIENCIA ergo-sum, 2024)
The concentrations of some atmospheric pollutants, including some considered greenhouse gases, were measured at different altitudes in the lower troposphere of the Orinoquía region (Colombia). Several sensors attached to an unmanned aerial vehicle (UAV) were used. The sensor system can capture the spatiotemporal variations of some atmospheric pollutants and meteorological variables. Vertical distribution patterns of pollutant concentrations monitored in the lower troposphere were mainly correlated with the temperature gradients, relative humidity, and solar radiation. CO 2 concentrations ranged from 72.3 to 646.5 ppm, for a mean value of 130.1 ppm.